Pemanfaatan teknologi berbasis game wordwall dalam meningkatkan minat dan hasil belajar siswa pada pembelajaran pendidikan agama islam - Jahrona Harahap; Ahmad Darlis (Indonesian Counselor Association (IKI), 2025)
This study aims to examine the implementation, student responses, interest, improvement in learning outcomes, and challenges in utilizing the game-based Wordwall technology to enhance student interest and achievement in Islamic Religious Education (PAI) at SDN Lubuk Pakam. The research employs a qualitative method with a field research approach. The data analysis techniques used include data reduction, data presentation, and conclusion drawing.The findings show that the use of Wordwall media in Grade IV PAI learning at SDN Lubuk Pakam is effective in increasing students' interest, engagement, and learning outcomes. Students responded positively to this media, as it made learning more interactive and enjoyable. Although there were challenges such as unstable internet connectivity and low digital literacy, these obstacles can be addressed through proper training and infrastructure support. It is recommended that teachers continue to use interactive media like Wordwall to support PAI learning, The school should provide supporting facilities such as a stable internet connection and ICT training for both students and teachers to ensure the optimal and sustainable use of digital media.